Sob o signo do "novo sindicalismo": das mudanças de identidade e de estratégia, na trajetória do PT e da CUT, à consolidação do populismo sindical no Governo Lula - Oliveira, Merilyn Escobar de (2008)
During the first mandate of Lula s government, the link between PT and CUT became object of a diversity of political analyses. They shared interests in some matters: The relation between party and labor union, the syndicalists role in this government and Lula s figure as a masses leader. This research intends to study the connection that prevailed among CUT, the workers Party and the administration of PT, and to identify how the changes in politics of the two organizations resulted in the configuration of a specific type of populism. The work is divided into three chapters. The first one examines the important interpretations about Lula s government. The second intends to check the changes expressed in official documents according to the dynamics of two variables, the identity and the strategy. The last chapter suggests some elements on the performance that the Union Central had in the administration of PT. The obtained results point to the predominance of the malleability of the strategic goals, the subsequent dilution of the classicist identity and the ideology consolidation of the union populism